Interventional pain management practices in Pakistan: The role of Physical Medicine and Rehabilitation (PMR) - Uzma Akhlaque; Sarah Razaq; Hakan Gunduz; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
Chronic pain represents a complex, multifaceted challenge that surpasses the prevalence of commonly encountered disorders such as diabetes mellitus and hypertension. This condition exerts a substantial burden on healthcare systems due to its pervasive impact. While pain interventions and procedures constitute a crucial facet, they alone do not constitute a comprehensive solution. Nevertheless, the strategic and precise application of these procedures by well-trained and proficient physicians offers patients a swift route to resuming their normal activities, sparing them from protracted reliance on medications. Within the realm of Physical Medicine and Rehabilitation (PM&R), Interventional Pain Management (IPM) adopts a multidisciplinary rehabilitative approach, addressing all dimensions of pain syndromes. This approach culminates in enhanced functional outcomes and an improved quality of life. This concise review underscores the significance of this integrated approach, shedding light on various pain procedures routinely employed for diagnostic and therapeutic purposes. Within this context, we briefly explore the application of ultrasound and C-arm guided procedures. In conclusion, this review underscores the imperative nature of embracing a multidimensional approach to pain management, essential for seamlessly incorporating interventional pain management techniques into the broader domain of rehabilitation medicine.